2020
DOI: 10.1186/s13002-020-00369-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoveterinary plants of Pakistan: a review

Abstract: Background: Ethnoveterinary medicine is crucial in many rural areas of the world since people living in remote and marginal areas rely significantly on traditional herbal therapies to treat their domestic animals. In Pakistan, communities residing in remote areas, and especially those still attached to pastoralist traditions, have considerable ethnoveterinary herbal knowledge and they sometimes use this knowledge for treating their animals. The main aim of the study was to review the literature about ethnovete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 65 publications
4
30
2
1
Order By: Relevance
“…Similar studies have also been reported from other parts of world where participants mostly use the members of Leguminosae/Fabaceae for the preparation of EVM for the treatment of different livestock diseases ( 10 , 85 87 ). However, the findings differ from those of other EVM studies in which the other families such as Apiaceae ( 88 ), Poaceae ( 30 ), Aloaceae ( 22 ), Asteraceae ( 89 , 90 ) and Solanaceae ( 91 ) were ranked as the highest. The difference among these studies may be related to the dominant vegetation of the areas or cultural significance ( 30 ).…”
Section: Resultscontrasting
confidence: 99%
“…Similar studies have also been reported from other parts of world where participants mostly use the members of Leguminosae/Fabaceae for the preparation of EVM for the treatment of different livestock diseases ( 10 , 85 87 ). However, the findings differ from those of other EVM studies in which the other families such as Apiaceae ( 88 ), Poaceae ( 30 ), Aloaceae ( 22 ), Asteraceae ( 89 , 90 ) and Solanaceae ( 91 ) were ranked as the highest. The difference among these studies may be related to the dominant vegetation of the areas or cultural significance ( 30 ).…”
Section: Resultscontrasting
confidence: 99%
“…The highest agreements (ICF = 0.87) in using ten taxa of the 68 reported events was observed to cure bloating (Table 6) and this might indicate the ailment is common to the surveyed agroclimatic zones and the ethnoveterinary plants found to be conventionally effective in treating the ailment. This agrees with Ahmed and Murtaza [9], Aziz et al [10], Luleka et al [12], who observed that a high ICF value is allied to a few target plant species with high use reports in in treating a speci c disease category and for screening bioactive compounds. In general the UV, FL (%), RFCs and ICF values vary depending on locality, nature of vegetation and geo-climate [47,51] and therefore their higher medicinal citations for a particular livestock disease treatment, for example, as observed in hot agroclimatic zone, could be ascribed to higher disease prevalence in this area which probably boosts the awareness of the traditional healers to formulate plant remedies for their livestock diseases than the witchdoctors in temperate and cool climatic zones.…”
Section: Discussionsupporting
confidence: 91%
“…It is concerned with the systematic investigation of the folk beliefs, knowledge, method and socio-cultural practices of the local community [6,7]. It also explores the animal breeding and feeding system; traditional surgical techniques; magico-religious practices and so forth [8][9][10]. In fact, this practice has been experienced by the indigenous people for a century in a way of formulating and using herbal remedies to handle animal health care and increasing the quality of animal-based food products [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Communities living in rural areas and far away from towns and cities depend on plant-based medicines for common diseases, and the usage of medicinal plants for the treatment of diseases is a common practice (Fayaz et al 2019. Ethno-veterinary knowledge is often conveyed mostly through oral transmission (Aziz et al 2020, Dutta et al 2021b, Nfi et al 2001. This traditional oral knowledge is declining due to improper documentation, the death of elder members of the tribe or community, rapid modernization, and lack of interest of the younger generation towards traditional practices (Bhatia et al 2014, Idu et al 2011, Kala et al 2006.…”
Section: Introductionmentioning
confidence: 99%